2019
DOI: 10.1103/physrevmaterials.3.124604
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity tensor of βGa2O3 analyzed by van der Pauw measurements: Inherent anisotropy, off-diagonal element, and the impact of grain boundaries

Abstract: The semiconducting oxide β-Gallium Oxide (β-Ga 2 O 3 ) possesses a monoclinic unit cell whose low symmetry generally leads to anisotropic physical properties. For example, its electrical conductivity is generally described by a polar symmetrical tensor of second rank consisting of four independent components. Using van der Pauw measurements in a well-defined square geometry on differently-oriented high-quality bulk samples and the comparison to finite element simulations we precisely determine the ratio of all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The large number of structural phases and the strong anisotropy of β-Ga 2 O 3 present difficulties for theoretical approaches. Nevertheless, previous theoretical work carried out on Ga 2 O 3 polymorphs focuses on various properties, for example, optical response, electron transport, electronic structure, and X-ray absorption spectra, calculated at different levels of computational expense and accuracy. Experimental studies predominantly consider material growth and optical properties with more extensive information available for the β-phase. , Very few studies to date combine theory and experiment, thus leaving some doubt over the accuracy of calculations and uncertainty in the understanding and interpretation of experimental data. ,, Overall, little information is available for the polymorphs of Ga 2 O 3 and studies considering a set or subset of the polymorphs are extremely rare. However, comparative studies of the polymorphs are invaluable for discerning trends between the different structures and advancing our understanding of the material.…”
Section: Introductionmentioning
confidence: 99%
“…The large number of structural phases and the strong anisotropy of β-Ga 2 O 3 present difficulties for theoretical approaches. Nevertheless, previous theoretical work carried out on Ga 2 O 3 polymorphs focuses on various properties, for example, optical response, electron transport, electronic structure, and X-ray absorption spectra, calculated at different levels of computational expense and accuracy. Experimental studies predominantly consider material growth and optical properties with more extensive information available for the β-phase. , Very few studies to date combine theory and experiment, thus leaving some doubt over the accuracy of calculations and uncertainty in the understanding and interpretation of experimental data. ,, Overall, little information is available for the polymorphs of Ga 2 O 3 and studies considering a set or subset of the polymorphs are extremely rare. However, comparative studies of the polymorphs are invaluable for discerning trends between the different structures and advancing our understanding of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the behaviour reported in [ 11 ] as a function of temperature could be extrapolated for higher temperatures, it is not straightforward that this would be a good approaching fact since it has already been reported that other properties of β-Ga 2 O 3 do not show the same behaviour at temperatures below room temperature and at higher temperatures. For example, the electrical conductivity shows a much sharper change at temperatures below 300 K than above [ 20 ]. The trend is the same but the rate of variation is quite different.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the data reported in this work quantitatively show an at least (lower estimate due to series resistances, see Figure 7) one order of magnitude higher in‐plane resistivity (i.e., charge carriers crossing domain interfaces) than out‐of‐plane resistivity (i.e., charge carriers flowing along the vertically oriented domains), in line with previously reported qualitative experimental data. [ 30 ] In this framework it is important to stress out that theoretical [ 50,57 ] and experimental [ 29 ] works on κ‐Ga 2 O 3 as well as the comparison among similarly structurally anisotropic oxides (e.g., β‐Ga 2 O 3 [ 58 ] and SnO 2 [ 59 ] ) exclude the possibility that the extent of this highlighted (lower bound) anisotropy could be possibly related to the pure orthorhombic structure of Ga 2 O 3 . The measurements here reported have been performed on nominally undoped samples (ΦSiH4= 0\[{\Phi _{{\rm{Si}}{{\rm{H}}_4}}} = \;0\], maximum domain dimension around 20 nm, see Figure 3) deposited on GaN templates; this has been done to avoid the presence of SiO x precipitates (confined in the first 200–300 nm close to the substrate interface in layers deposited with ΦSiH4${\Phi _{{\rm{Si}}{{\rm{H}}_4}}}$, see Figure 4) that could potentially interfere in the out‐of‐plane R measurements.…”
Section: Discussionmentioning
confidence: 99%